Pengaruh Indeks Pembangunan Manusia (IPM) dan Produktivitas Tenaga Kerja Terhadap Tingkat Kemiskinan di Provinsi Gorontalo - Nadiah Putri Cecar Rasyid; Fitri Hadi Yulia Akib; Irawati Abdul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of the Human Development Index (HDI) and labor productivity on poverty levels in Gorontalo Province. This study used secondary data in the form of panel data from 2018 to 2024 obtained from Statistics Indonesia (BPS). The unit of analysis covered all cities and regencies in Gorontalo Province, and the research variables included HDI, labor productivity, and poverty levels. This study used a panel data regression analysis in Stata to examine both the individual and simultaneous effects of the independent variables on poverty levels. Based on the analysis, HDI has a negative and significant effect on poverty levels, while labor productivity also exhibits a negative effect, with a smaller influence. Simultaneously, both variables are statistically significant in explaining variations in poverty levels in Gorontalo Province. These results indicate that improvements in HDI, particularly through enhanced education and healthcare, as well as increases in labor productivity through training, technological adoption, and job creation, are essential strategies for reducing poverty in the region.